Hydrodynamic performances of a wall type breakwater - a physical and numerical approach - Viswanathan, Kumaran; Manu; Rao, Subba (Journal of Naval Architecture and Marine Engineering, 2021)
In this paper, hydrodynamic characteristics of caisson type breakwater are investigated through physical model approach and a numerical model based on the Volume of Fluid (VOF) is validated. The investigations are carried out for varying wave characteristics and depth of water 0.50 m. In an experimental study, to understand the model and scale effects for the desired wave conditions is a critical task in all-time conditions. So, it is also necessary to develop an appropriate numerical model to understand the hydrodynamics of the selected test model. Using the Volume of Fluid (VOF) method and incompressible open channel fluid flow a 2D numerical wave flume is developed using ANSYS- Fluent platform. The wave boundary conditions are adopted by solving the Reynolds-Averaged Navier Stokes equations (RANS equation) and especially with k—ε model to examine the effects of turbulence on the numerical results. The wave forces, wave runup, and wave reflection characteristics on the test model are measured for different wave characteristics, and results obtained from the numerical investigations are comparable with the experimental results to evident the relevance of the developed numerical model.